Case report: Adult case of A20 haploinsufficiency suspected as neuro-Behçet disease - Shirai, Harumi; Saito-Sato, Naoko; Horiuchi, Emiko; Kikuchi, Hirotoshi; Kadowaki, Saori; Ohnishi, Hidenori; Suzuki, Takeshi (Frontiers in Immunology, 2025)
Patients with A20 haploinsufficiency (HA20) presenting with central nervous system (CNS) symptoms are rare, and available reports are limited. Here, we describe a patient with HA20, previously followed up as Behçet disease, who presented with CNS symptoms in adulthood. A 38-year-old Japanese male who had been followed up for incomplete Behçet disease at another hospital since 28 years of age presented to our hospital with acute-onset diplopia and persistent hiccups that were severe enough to cause vomiting. Despite suspicion of neuro-Behçet disease on the basis of the patient’s medical history, a definitive diagnosis could not be made. He experienced transient episodes of diplopia over a short period, and brain magnetic resonance imaging T2 fluid-attenuated inversion recovery images revealed nonspecific hyperintensities in the cerebral white matter. He was initially managed with low-dose prednisolone and colchicine but continued to experience low-grade fever, recurrent oral ulcers, and genital ulcers. A gene panel test for periodic fever syndromes revealed a variant in the TNFAIP3 gene, showing a c.259C>T nonsense variant. As previous reports have described the same variant in patients with HA20, the patient was diagnosed with HA20. The patient’s response to glucocorticoids and colchicine therapy was limited, and his symptoms improved upon initiation of tumor necrosis factor-α inhibitor therapy. The variant showing a c.259C>T nonsense variant in the TNFAIP3 gene has been previously reported in China and France, making this the first report in Japan, which is considered a rare instance of HA20 with CNS involvement.